(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
This article highlights the formation of Ethnolinguistics as an independent linguistic network, the inextricable connection of nationality and language in the history of peoples, the study of early Ethnography in Uzbek linguistics and the importance of ethnolinguistics in the process of globalization.